Socio-economic determinants and impact of adopting climate-smart Brachiaria grass among dairy farmers in Eastern and Western regions of Kenya - Maina, Kevin W.; Ritho, C.N.; Lukuyu, Ben A.; Rao, E.J.O. (Elsevier, 2020)
The sustainability of the livestock sector in sub-Saharan Africa is negatively affected by limited access to high-quality fodder in adequate quantities. The effects of climate change further exacerbate feed availability. Therefore, there is a need to develop feasible cost-effective strategies for improving the year-round feed supply. Improved planted forages such as Brachiaria grass have been recommended as one of the strategies of alleviating feed scarcity, especially in drier agro-ecological zones. This study analyses the socio-economic determinants of adoption and the impact of adopting Brachiaria grass for feed sufficiency and increased milk production. Propensity Score Matching (PSM) method was used to assess the determinants and impact of the adoption of Brachiaria grass. Empirical results indicate that the adoption of Brachiaria grass led to a significant increase in milk production by 27.6% and feed sufficiency by 31.6%. The positive impact of Brachiaria grass is consistent with the role of agricultural technologies in improving the productivity, income, and welfare of smallholder farmers. The adoption of Brachiaria grass is influenced by age of farmer, tropical livestock unit (TLU), type of animal breed, perceived benefits of the technology, access to extension, and farmer group membership. The study recommends holistic policy approaches that promote the widespread adoption of Brachiaria grass. There is also a need for an effective information dissemination pathway for Brachiaria grass.